Etanercept and sulfasalazine, alone and combined, in patients with active rheumatoid arthritis despite receiving sulfasalazine: a double-blind comparison. Issue 10 (10th April 2006) - Combe, B; Codreanu, C; Fiocco, U; Gaubitz, M; Geusens, P P; Kvien, T K; Pavelka, K; Sambrook, P N; Smolen, J S; Wajdula, J; Fatenejad, S
Abstract : Objective: To compare the efficacy and safety of etanercept and sulfasalazine, alone and in combination, in patients with active rheumatoid arthritis despite sulfasalazine treatment. Methods: A double-blind, randomised study in adult patients with active rheumatoid arthritis despite stable sulfasalazine (2–3 g/day) treatment. The primary end point was a 20% response by the American College of Rheumatology (ACR) criteria at 24 weeks. Results: At baseline, the three treatment groups (sulfasalazine, n = 50; etanercept, n = 103; etanercept and sulfasalazine, n = 101) were comparable for demographic variables and disease activity. Lack of efficacy was the primary reason for discontinuation (sulfasalazine, n = 12; etanercept, n = 1; etanercept and sulfasalazine, n = 4; p<0.001). Significantly more patients receiving etanercept, alone or in combination (74% for each), achieved ACR 20 responses at 24 weeks than those receiving sulfasalazine (28%; p<0.01). Similarly, more patients in the etanercept groups achieved ACR 50 and ACR 70 responses than those in the sulfasalazine group (p<0.01). In the groups receiving etanercept, significant differences in the ACR core components were observed by week 2 compared with those receiving sulfasalazine alone (p<0.01). The incidences of several common adverse events (headache, nausea, asthenia) were lower with etanercept alone than with the combination (p<0.05), but infections and injection site reactions were higher with etanercept alone (p<0.05). The safety profiles of both etanercept treatment groups were comparable with previous experience of etanercept. Conclusions: For all efficacy variables assessed, etanercept alone or in combination with sulfasalazine resulted in substantial and similar improvement in disease activity from baseline to week 24 compared with sulfasalazine alone in patients with active rheumatoid arthritis despite their sulfasalazine treatment. All three treatments were generally well tolerated.